Deliverable 6.15 Risk Assessment System - Aarnes, Øivin; Brude, Odd-Willy (Zenodo, 2021)
The motivation for developing an integrated risk assessment system is to provide insights and to simplify the process of integration, analysis and use of INTAROS data within Arctic marine risk assessments. This will support business planning and development in the Arctic region. The risk assessment system has been built upon “The Arctic Risk Map” (https://maps.dnvgl.com/arcticriskmap/), a system designed to present data from the Arctic marine environment in an easily accessible way with focus on clear and transparent communication. The selected use case is focused on sea ice extent and concentration with some supplemental parameters. Main data sources for the current version of the system area 30-year climatology on sea ice from the National Snow and Ice data Centre (NSIDC) and the Arctic ocean–sea ice reanalysis for the period 2007–2016from University of Hamburg (UHAM). The report describes a first implementation of the Risk Assessment system. It addresses the data sources and system functionality to visualise and analyse the data. The system will be further improved and enhanced until the end of the INTAROS project period and will be made available at DNV ArcGIS server. As an end user product, access to and use of the Risk Assessment system will further support the implementation of the INTAROS roadmap (D1.10) towards a future Sustainable Arctic Observing System (SAOS) based on the synthesis of results from INTAROS.